The impact of theological foundations of restorative justice for the human rights protections of North Korean stateless women as victims of human trafficking - Yoon, I Sil 19XX- (HTS teologiese studies, 2019)
Restorative justice, with its most prominent characteristic being rebuilding social relationships among victims, perpetrators and the community that was damaged by a crime, has been proposed as an alternative to the traditional retributive justice model to treat criminal acts. Both secular and religious groundings exist for restorative justice, and religious theorists have developed theological groundings for restorative justice based on scripture and other sources. In this article, I will explore how a theologically grounded restorative justice model, focusing on Christopher Marshall’s theological exposition of restorative justice, can contribute to the thought and action of Christians and the larger public in the face of the moral injury caused by human trafficking. I will address how this model can also contribute to social structural change. In my analysis, I will employ a case study of North Korean stateless women who reside in China and who are victims of human trafficking.